Towuntu Theology: A Study of Efforts to Achieve the Welfare of the GMIM Moriah Tawuntu Church - Mandalele, Jenins Boy; Ratag, Patricia Linda; Kula, Agustince Neti (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The purpose from this research is describe the meaning of Theology Towuntu within analyzed of theology effort to increase well-being in Christian Evangelical Church Minahasa Moriah Towuntu, Pasan of Sub-district, Southeast Minahasa of Regency, North Sulawesi of Prevence. This research used qualitative of methode on basic to philosophy “postpositivisme” or “inteprestative” can say is method naturalistic qualitative research with process inductive, the purpose this methode is to finding meaning from data of analyzed. This research used analyzed literature review, as general method with to depend on The Holy Bible and other document of church as the main source. The result of research describing that “Theology Towuntu” according of etymology are the group who believe to Jesus Christ to bring well-being to the member. Philosophy “Theology Towuntu” can approved with ontology, epistemology dan axiology. Reflection of Missiology in form pastoral care “Theology Towuntu are established Forum conscious child, within it are group Senior High School Student and college student have the purpose to achieve agreement contract between the student/college student with the parents, they are will do it in agreement contract such as student finishing the study with good and the parent can buy the study too, thus the student will work and achieve well-being with parents.